2013
DOI: 10.1161/circgenetics.113.000054
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiac Phenotype in Patients With a CHD7 Mutation

Abstract: Background— Loss-of-function mutations in CHD7 cause Coloboma, Heart Disease, Atresia of Choanae, Retardation of Growth and/or Development, Genital Hypoplasia, and Ear Abnormalities With or Without Deafness (CHARGE) syndrome, a variable combination of multiple congenital malformations including heart defects. Heart defects are reported in 70% to 92% of patients with a CHD7 mutation, but most studies are small and do not provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 37 publications
4
67
0
Order By: Relevance
“…Congenital heart defects occur in 74% of patients who have CHARGE syndrome due to a CHD7 mutation, and in 80% of patients with a truncating CHD7 mutation [3]. Our previous study showed that while the types of heart defects found in CHARGE syndrome patients are variable, atrioventricular septal defects and conotruncal defects are overrepresented compared to typically non-syndromic heart defects [3].…”
Section: Introductionmentioning
confidence: 96%
“…Congenital heart defects occur in 74% of patients who have CHARGE syndrome due to a CHD7 mutation, and in 80% of patients with a truncating CHD7 mutation [3]. Our previous study showed that while the types of heart defects found in CHARGE syndrome patients are variable, atrioventricular septal defects and conotruncal defects are overrepresented compared to typically non-syndromic heart defects [3].…”
Section: Introductionmentioning
confidence: 96%
“…The severity and spectrum of congenital heart defects had been thought to vary [9]. It is recently reported that conotruncal defects and atrioventricular septal defects are overrepresented in patients with CHD7 mutations compared with patients with nonsyndromic heart defects [10]. Tetralogy of Fallot was relatively frequent among the conotruncal defects, whereas interrupted aortic arch, double outlet right ventricle, and truncus arteriosus were less frequently seen.…”
Section: Discussionmentioning
confidence: 99%
“…Since CHD7 causes congenital heart defects in most people harboring a pathogenic CHD7 mutation (Corsten-Janssen et al, 2013), several studies have analyzed CHD7 in cohorts of patients with cardiovascular malformations and an overview of these studies is shown in Table 1. Screening of only CHD7 in a cohort of 67 patients with isolated heart defects (Qi et al, 2008) and in a cohort of 46 patients selected for their type of heart defect and one other feature of CHARGE syndrome (Corsten-Janssen et al, 2014) identified no pathogenic mutations.…”
Section: Chd7 Mutations In Cohorts Of Patients With Heart Defectsmentioning
confidence: 99%
“…The combination of AVSD, outflow tract defects and PDA encompasses about 52% of the heart defects in the CHD7 mutation group but these defects represent only 12% in the non-syndromic group. Figure adapted from (Corsten-Janssen et al, 2013). AVSD, atrioventricular septal defects; LVOTO, left ventricular outflow tract obstruction; OFT, outflow tract defects; PDA, patent ductus arteriosus; RVOTO, right ventricular outflow tract obstruction major CHARGE feature.…”
Section: Chd7 Mutations In Cohorts Of Patients With Heart Defectsmentioning
confidence: 99%
See 1 more Smart Citation